(untitled) (Research, Society and Development, 2022)
Hospital malnutrition affects negatively in the treatment of the cure of pathologies that can lead to the quality of life of hospitalized individuals. The importance of adequate nutrition for these patients guarantees not only the improvement of the clinical picture but also the restoration of the patient’s well-being. The aim of the study was to investigate the comparison of nutritional screening methods in hospitalized patients using questionnaires. In addition to performing anthropometry to identify possible nutritional risks and hospital malnutrition. The screening methods may subjectively indicate some deficiencies of nutrients that may lead to an alleged malnutrition. This research was conceived from nutritional screening methods (Malnutrition Universal Screening Tool, Nutrition Risk Screening 2002 and Subjective Global Assessment) in hospitalized patients, based on scientific studies on these devices in order to preserve the life guarantee and evolution of research on hospital malnutrition. The NRS 2002 if presented more completely than other methods but the methods were of results next. Hospitals must standardize effective and cheap methods of rapid application for inpatients.